Variation of Human Values and Modernization: Preliminary Results. (April 2020) - Korotayev, Andrey; Slinko, Elena; Meshcherina, Kira; Zinkina, Julia
The current article investigates the relation between values and modernization applying some elements of the method proposed by Inglehart and Welzel (the authors of the Human Development Sequence Theory) to the data of Shalom Schwartz. The values survey by Schwartz specifies two main value axes, namely, conservation versus openness to change and self-transcendence versus self-enhancement. Our research has revealed that the correlation between these two value axes differs in its direction when estimated for "macro-Europe" (that includes Europe and former settlement colonies of North and South America and Oceania) and "Afroasia" (that includes Asia and Africa). In "macro-Europe, " we deal with a significant positive correlation between openness to change and self-transcendence, whereas in "Afroasia, " this correlation is strong, significant, and negative. We investigate the possible impact of modernization on this difference. To do this, we approximate modernization through such indicators as gross domestic product (GDP) per capita and the proportions of the labor force employed in various sectors of economy. We find that, in both megazones, modernization is accompanied by increasing openness to change values. As for the self-transcendence/self-enhancement axis, we propose two possible explanations of the different dynamics observed in Europe and in "the East" (Asia and North Africa), namely, (a) that Eastern and Western societies find themselves at different modernization stages and (b) that this difference is accounted for by different civilizational patterns. Further analysis suggests that the latter explanation might be more plausible.